AN ANALYSIS OF THE TRANSLATION OF TABOO WORDS IN CENTRAL INTELLIGENCE MOVIE - Luthfira Isnaeni Widhi; Neneng Sri Wahyuningsih; Sulistini Dwi Putranti (STBA LIA - Jakarta, 2019)
This study is about an analysis of the translation of taboo words in “Central Intelligence” movie. It is to shed the type of taboo words and the procedures applied to translate the taboo words. The theories used in this study are from Timothy Jay (1992) to classify the types of taboo words and a theory from Peter Newmark (1987) to analyze the translation procedures. The data are taken from the movie entitled Central Intelligence by choosing 20 data out of 65 data of taboo words. The result of the analysis shows that are seven translation procedures employed in the translation of taboo word. They are cultural equivalent (seven data), reduction (four data), functional equivalent (three data), paraphrase (three data), naturalization, through translation and literal translation (one data each). For the types of the taboo words, the result shows that there are eight types of taboo words of the 20 selected data. They are insult and slurs (four data), profanity (one data), taboo (two data), epithets (three data), slang (four data), scatology (one data), vulgarity (three data) and cursing (two data) of ten types proposed by Timothy Jay. From this study, it is concluded that the taboo words from the SL cannot always be translated into the taboo words in the TL because of the cultural differences.